Meningkatkan Produktivitas Karyawan Melalui Pemberdayaan, Kerja Sama Tim dan Pelatihan di Perusahaan Jasa - Prabawa, I Made Adi; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p19, 2018)
An increased productivity provides a competitive advantage for a company. This research aim to understand the impact of empowerment, teamwork, and training on workforce productivity. The research takes place in Unagi Spa Bali, and 40 employees participate as sample. Data were collected by questionnaire then measured using Likert scale score. Multiple Linear Regression is used to analyze. The result indicates that each variable empowerment, teamwork and training partially has a positive and significant impact on workforce productivity at Unagi Spa Bali. Empowerment is considered as one of key to success in maximizing productivity. Teamwork is also key feature of successful management aimed to improve overall outcomes of productivity. An effective training helps to create an efficient workforce productivity.   Keywords: empowerment, teamwork, training and employee productivity.